2022
DOI: 10.1021/acsnano.2c04846
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Thermal and Nonthermal Hot Electron Tunneling Inside a Photoexcited Tunnel Junction

Abstract: Efficient operation of electronic nanodevices at ultrafast speeds requires understanding and control of the currents generated by femtosecond bursts of light. Ultrafast laser-induced currents in metallic nanojunctions can originate from photoassisted hot electron tunneling or lightwave-induced tunneling. Both processes can drive localized photocurrents inside a scanning tunneling microscope (STM) on femto- to attosecond time scales, enabling ultrafast STM with atomic spatial resolution. Femtosecond laser excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Notably, the divergence observed in PES relative to the EOS result is more significant than that in TDFES. This distinction can be attributed to the different regions where the two methods are applied and the potential influence of the incident visible light pulse in PES, whose result is varied with the laser strength . Specifically, PES waveforms were measured by using photoemission current from the sample side, which may be susceptible to thermal effects from the sample.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the divergence observed in PES relative to the EOS result is more significant than that in TDFES. This distinction can be attributed to the different regions where the two methods are applied and the potential influence of the incident visible light pulse in PES, whose result is varied with the laser strength . Specifically, PES waveforms were measured by using photoemission current from the sample side, which may be susceptible to thermal effects from the sample.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…This distinction can be attributed to the different regions where the two methods are applied and the potential influence of the incident visible light pulse in PES, whose result is varied with the laser strength. 31 Specifically, PES waveforms were measured by using photoemission current from the sample side, which may be susceptible to thermal effects from the sample. Nevertheless, it has been demonstrated that relying solely on the sample photoemission current is sufficient for retrieving the near-field waveforms.…”
Section: ■ Methods and Resultsmentioning
confidence: 99%
“…Hence, the electronic population at the tungsten tip at the Fermi level energy is modulated via the formation of hot electrons. 36 Meanwhile, free carriers and free excitons are simultaneously created at various energies, ranging from 1.55 eV (800 nm) to 1.03 eV (1200 nm) within the Si(100) conduction band, specifically from the top of the Si π* orbital band to the lower edge of the conduction band. This transient electronic population change may significantly affect the charge state of the STM junction and hence the shape of the tunnel barrier.…”
Section: Resultsmentioning
confidence: 99%
“…When the laser wavelength is tuned from 800 to 1200 nm, the irradiated zone that surrounds the STM junction promotes the formation of a large number of free charge carriers in the silicon surface as well as hot electrons in the STM tip. Hence, the electronic population at the tungsten tip at the Fermi level energy is modulated via the formation of hot electrons . Meanwhile, free carriers and free excitons are simultaneously created at various energies, ranging from 1.55 eV (800 nm) to 1.03 eV (1200 nm) within the Si(100) conduction band, specifically from the top of the Si π* orbital band to the lower edge of the conduction band.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the coherent manipulation of light–matter interactions can now occur with atomic accuracy, which may provide an alternate approach to switch the quantum state population of a qubit. Even though TR-STM is currently a sophisticated technique only available in a limited number of research laboratories, recent advances in technology have made TR-STM more accessible and user-friendly. ,,,,, Because of its versatility, we highly anticipate its future as a widely used technique that is accessible to users in a diverse array of fields.…”
Section: Discussionmentioning
confidence: 99%